2004
DOI: 10.5194/acp-4-323-2004
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of aerosol particles composed of protein and saltswith water vapor: hygroscopic growth and microstructural rearrangement

Abstract: Abstract. The interaction of aerosol particles composed of the protein bovine serum albumin (BSA) and the inorganic salts sodium chloride and ammonium nitrate with water vapor has been investigated by hygroscopicity tandem differential mobility analyzer (H-TDMA) experiments complemented by transmission electron microscopy (TEM) and Köhler theory calculations (100-300 nm particle size range, 298 K, 960 hPa). BSA was chosen as a well-defined model substance for proteins and other macromolecular compounds, which … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
174
0
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(197 citation statements)
references
References 115 publications
18
174
0
5
Order By: Relevance
“…Kerminen (1997) estimated the necessary residence time for achievement of water equilibrium of aqueous droplets to be between 0.005 and 0.1 s (water uptake coefficient α w = 0.001, 25 • C) for 100 and 500 nm particles, respectively. Therefore, the typical residence time of a few seconds in the humidification or dehumidification section in a HTDMA measurement is assumed to be sufficient for most equilibrium hygroscopicity measurements (Brooks et al, 2004;Mikhailov et al, 2004). Moreover, our HGF results for the three pure organic components are in good agreement with data by Mochida and Kawamura, (2004), Brooks et al (2004), and conducted with different techniques and/or residence times.…”
Section: Gf Of Mixtures Of Organic Surrogate Compounds + Ammonium Sulsupporting
confidence: 80%
See 1 more Smart Citation
“…Kerminen (1997) estimated the necessary residence time for achievement of water equilibrium of aqueous droplets to be between 0.005 and 0.1 s (water uptake coefficient α w = 0.001, 25 • C) for 100 and 500 nm particles, respectively. Therefore, the typical residence time of a few seconds in the humidification or dehumidification section in a HTDMA measurement is assumed to be sufficient for most equilibrium hygroscopicity measurements (Brooks et al, 2004;Mikhailov et al, 2004). Moreover, our HGF results for the three pure organic components are in good agreement with data by Mochida and Kawamura, (2004), Brooks et al (2004), and conducted with different techniques and/or residence times.…”
Section: Gf Of Mixtures Of Organic Surrogate Compounds + Ammonium Sulsupporting
confidence: 80%
“…The organic particles measured are likely always in the effloresced, i.e., crystalline, state apparently even at high RH. The apparent increase in diameter during dehumidification may be explained by particle shape restructuring since the (poly)crystalline particles are likely nonspherical at dry conditions but may become more sphere-like in shape when exposed to higher RH (Mikhailov et al, 2004). Also, no ERH of 4-hydroxybenzoic acid in the dehydration mode was observed during the experiments; the likely reason is that the highest RH reached in the humidifier was approximately 98 %, which may be below the ERH of 4-hydroxybenzoic acid, reported as above 98 % RH in another study (Mochida and Kawamura, 2004).…”
Section: Gf Prediction By Zsrmentioning
confidence: 99%
“…On the other hand volatile aerosol particles may suffer from evaporation artefacts inside the HTDMA if the residence time exceeds a few tens of seconds. and Mikhailov et al (2004) demonstrated that this artefact can occur for ammonium nitrate particles. It can be expected that also other compounds (e.g.…”
Section: Residence Time Of the Aerosol At High Rhmentioning
confidence: 99%
“…Moreover, κ values determined by HTDMA measurements can be different from κ values determined by CCN measurements, because of the general dependence of κ and equivalent hygroscopicity parameters (van't Hoff factor and osmotic coefficient) on solute concentrations (Mikhailov et al, 2004(Mikhailov et al, , 2009Rose et al, 2008;Reutter et al, 2009) and potential solubility effects (Petters and Kreidenweis, 2007).…”
Section: Uncertainties and Validationmentioning
confidence: 99%